Support and information needs following a diagnosis of dementia with Lewy bodies. (2nd September 2015) - Killen, Alison; Flynn, Darren; De Brún, Aoife; O'Brien, Nicola; O'Brien, John; Thomas, Alan J.; McKeith, Ian; Taylor, John-Paul
ABSTRACT: Background: There is a lack of knowledge regarding the information and support needs of people with dementia with Lewy bodies (DLB) and their families around the time of diagnosis. Methods: A volunteer sample of patients with DLB and their family members completed a web survey hosted by the UK based Lewy Body Society in May 2014. This focused on past experiences of information and support received and what information and support needs would have been beneficial at the time of diagnosis. Results: One hundred and twenty five adults responded to the survey. The majority were first degree relatives or spouses of people with DLB ( n = 107, 86%). Approximately 50% ( n = 61) reported they had not received any tangible support at diagnosis. Thirteen categories of information needs were identified. Conclusions: People with DLB and their family members are currently inadequately supported at diagnosis. There is a need to address information needs related to symptomology, medication and prognosis, including provision of emotional and instrumental social support. Seeking the views of recipients of information and support is important in ensuring relevance and appropriateness prior to the development of interventions to improve the knowledge and coping skills of people with DLB and caregivers.